Liquid silicone rubber : chemistry, materials, and processing - Fink, Johannes Karl (John Wiley & Sons, Inc. ; Scrivener Publishing LLC, 2019)
"The scientific literature with respect to liquid functional rubbers is collected in this monograph. The text focuses on the basic issues and also the literature of the past decade. The book provides a broad overview of the materials used therein. In particular, materials and compositions for liquid functional rubbers are discussed. Also, methods of curing and special properties are described, such as tracking and erosion resistance, adhesion properties, storage and thermal stability. Methods of curing are precision casting, hybrid additive manufacturing, peroxide curing, ultraviolet curing, liquid injection molding, or hot embossing. Special fields of applications are automotive and underwater applications, electrical and optical uses, and medical uses"-- Provided by publisher
Keywords: Silicone rubber.; Rubber chemistry.; Rubber industry and trade.; elektronické knihy; electronic books